Handbook of neuroemergency clinical trials - Alves, Wayne M.; Skolnick, Brett Evan (Elsevier Academic Press, 2006)
During the 1990s, scientific advances in understanding the mechanisms and pathophysiology of acute central nervous system injury were offset by a history of disappointing results from Phase III clinical trials of novel neuroprotective drugs. Numerous novel compounds were tested, and seemingly fell by the wayside. This book is intended to focus on novel therapies and the unique challenges their intended targets pose for the design and analysis of clinical trials. The authors explore the issues facing research in this area and the strategies that might lead to future success in this critical area of unmet medical need. It represents a compendium of information gained from over 20 years of clinical trial experience in areas of acute neurology and neurosurgery. From the knowledge of clinical assessment using standardized tools, to the intricate design of difficult hyper-acute neuroemergencies trials, the reader will benefit from the authors' perspectives.